(untitled) (Bangladesh Journal of Pharmacology, 2015)
This study aims to evaluate the efficacy and safety of goserelin combined with chemotherapy for premenopausal women with breast cancer. Literatures were extracted from databases including Excerpta Medica Database, Springer, Pubmed, China National Knowledge Infrastructure and Chinese Biological Medicine from their inception up to May 2014. The main efficacy measures were 5 years overall survival (OS), 10 years OS, 5 years disease free survival and 5 years progress free survival. Ten randomized comparison clinical trials were eligible in this study. The result showed that goserelin combined with chemotherapy group can improve the survival rate and decrease the incidence of arthralgia in postmenopausal breast cancer patients, respectively, compared to the control group. However, they can increase the occurrence of vomiting during the chemotherapy process. Compared with the simple chemotherapy, goserelin combined with chemotherapy can provide benefits for premenopausal women with breast cancer on improving the survival rate and reducing arthralgia.